ADAM10 mediates N‐cadherin ectodomain shedding during retinal ganglion cell differentiation in primary cultured retinal cells from the developing chick retina. Issue 4 (18th February 2013) - Paudel, Sharada; Kim, Yeoun‐Hee; Huh, Man‐Il; Kim, Song‐Ja; Chang, Yongmin; Park, Young Jeung; Lee, Kyoo Won; Jung, Jae‐Chang
Abstract Here, we examined the role of ADAM10 during retinal cell differentiation in retinal sections and in vitro cultures of developing chick retinal cells from embryonic day 6 (ED6). Immunohistochemistry showed that ADAM10 is abundantly expressed in the inner zone of neuroblastic layer at ED5, and it becomes more highly expressed in the ganglion cell layer at ED7 and ED9. Western blotting confirmed that ADAM10 was expressed as an inactive pro‐form that was processed to a shorter, active form in control cultured cells, but in cultures treated with an ADAM10 inhibitor (GI254023X) and ADAM10‐specific siRNA, the level of mature ADAM10 decreased. Phase‐contrast microscopy showed that long neurite extensions were present in untreated cultures 24 h after plating, whereas cultures treated with GI254023X showed significant decreases in neurite extension. Immunofluorescence staining revealed that there were far fewer differentiated ganglion cells in ADAM10 siRNA and GI254023X‐treated cultures compared to controls, whereas the photoreceptor cells were unaltered. The Pax6 protein was more strongly detected in the differentiated ganglion cells of control cultures compared to ADAM10 siRNA and GI254023X‐treated cultures. N‐cadherin ectodomain shedding was apparent in control cultures after 24 h, when ganglion cell differentiation was observed, but ADAM10 siRNA and GI254023X treatment inhibited these processes. In contrast, N‐cadherin staining was strongly detected in photoreceptor cells regardless of ADAM10 siRNA and GI254023X treatment. Taken together, these data indicate that the inhibition of ADAM10 can inhibit Pax6 expression and N‐cadherin ectodomain shedding in retinal cells, possibly affecting neurite outgrowth and ganglion cell differentiation. J. Cell. Biochem. 114: 942–954, 2013. © 2013 Wiley Periodicals, Inc.